Wear performance of alumina based cutting tool when machined with AISI 1045 carbon steel - Mazda, Nur Syahirah (2018)
Latest developments in the manufacturing industry aim to produce high quality products with reduced time and cost. Automated and flexible manufacturing systems such as the computerized numerical control (CNC) machines are employed due to the capable of minimizing the processing time while achieving high accuracy. Machining essentially will produce high cutting temperature that reduce tool life. Tool wear is a paramount factor in determining tool life. It affects surface quality and precision of dimensions of the workpiece. Therefore, ceramic cutting tools are widely used for machining hard materials such as cast irons, alloy steels and carbon steels. These materials are so hard that they possess wide range of hardness and high temperature resistance due to high hot hardness and very good chemical stability (Whitney, 1994). Alumina cutting tool is commonly used for machining hard materials in high speed. It is also suitable for dry machining for its uniqueness in mechanical and chemical properties, especially at high temperature, such as high wear resistance, relatively low chemical reactivity with steels, high hot hardness, chemical inertness and high abrasion resistance (Deng et al., 2012). However, it is still expected that there will be temperature rise that may result to molten metal to cause material deformation. Another type of alumina cutting tool; alumina with zirconia reinforcement is said to offer an improved properties from the alumina based. The two types of ceramic cutting tool are fabricated and machined using AISI 1045 carbon steel to evaluate and compare the performance of tool wear and surface roughness of the workpiece. Results shows that both alumina and alumina-zirconia is capable to be fabricated as cutting tools and solidly represent the round shape of cutting tool with adequate hardness. Cutting tool fabricated with alumina and zirconia powder exhibited better wear performance as compared to the cutting tool with alumina only. The alumina-zirconia based cutting tool recorded a maximum of 200s tool life as compared to 145s for alumina based cutting tool. Surface roughness when AISI 1045 is machined with both cutting tools exhibited almost similar characteristics. Maximum value is recorded at 3.16 μm when machining with alumina-zirconia cutting tool after 150s. Whereas, minimum surface roughness is recorded at 0.67 μm with the same cutting tool type; the alumina-zirconia based which is at 150s cutting time. Wear development of cutting tool demonstrated uniform wear land at the early stage of machining before gradually notching at the specific region of wear before attachment of built up edge along cutting edges. For alumina based tool, the wear mechanism is dominated by the obvious formation of built up edge and adhesive wear. Whereas for alumina-zirconia based cutting tool, wear mechanism is dominated by the minor formation of built up edge and small particles detachment at the cutting edge.